An Analysis of Translation Techniques in Indonesian Subtittle in The Movie Entitled The Little Mermaid - Damayanti, Rosa Andriyana Dewi; Hardiany, Dewi Rosnita (Universitas Ngudi Waluyo, 2024)
Translation is an attempt to transfer meaning, ideas, or information from the source language (SL) to the target language (TL). This research aims analyze the translation techniques of English to Indonesian subtitles in the movie The Little Mermaid. Theory used in the study was by Molina & Albir (2002) to collect and analyze the data, while the method used in this study was a descriptive qualitative method. The total numbers found 1351 and the percentage of each technique are, literal translation occurs 1061 times (78,53%), reduction occurs 5 times (0,37%), generalization occurs 4 times (0,30%), linguistic compression occurs 69 times (5,11%), adaptation occurs 21 times (1,55%), modulation occurs 74 times (5,48%), transposition occurs 2 times (0,15%), borrowing occurs 58 times (4,29%), compensation occurs 1 times (0,07%), linguistic amplification occurs 7 times (0,52%), calque occurs 8 times (0,59%), Equivalent occurs 25 times (1,85%), Equivalent to Specified occurs 1 times (0,07%), Information occurs 2 times (0,15%), and amplification occurs 13 times (0,96%). The most dominant translation technique found in the movie The Little Mermaid is literal translation. And the translation techniques that are least used in translating the film The Little Mermaid are compensation and equivalent to specified. Keywords: Movie, Subtitle, Translation Techniques